Systematic review of single and combined treatments for different types of striae: a comparison of striae treatments. (16th June 2021) - Seirafianpour, F.; Sodagar, S.; Mozafarpoor, S.; Baradaran, H.R.; Panahi, P.; Hassanlouei, B.; Goodarzi, A.
Abstract: Striae distensae (SD) or stretch marks are among the most common forms of atrophic scarring and cosmetic problems, especially in women, that negatively affect quality of life. The main causes of SD vary widely, but the most significant ones include obesity, pregnancy, high corticosteroid levels, weight changes, endocrine disorders and genetic predispositions. Various modalities are available for the treatment of SD; however, there is still no gold standard therapy for this condition. Given the many questions concerning the preferred therapeutic modalities for SD or their overall cost‐effectiveness, this comprehensive systematic review discusses the most prevalent, recent and promising therapies for SD in three main categories, including single therapy, therapeutic comparisons and combination therapy. A systematic search was carried out in Medline, Scopus, Web of Science and Google Scholar for original articles published on the treatment of SD by 20 May 2019. One hundred articles were reviewed and divided into three categories. In the single therapy category, we found that laser and other light‐based devices and topical treatments are the most commonly applied interventions. In the therapeutic comparison category, we found that most of the common therapeutic modalities are equally effective and there is no significant difference between them in side‐effects and treatment duration. In the combination therapy category, we found that the combination of two or more modalities is usually better than using each one alone.